PENGEMBANGAN E-BOOK INTERAKTIF BERBASIS LITERASI VISUAL UNTUK MENINGKATKAN PEMAHAMAN TEKS SASTRA DI SMP - Anita Candra Dewi (JURNAL SKRIPTA, 2025)
This research aims to develop and test the effectiveness of interactive e-books based on visual literacy in improving students' understanding of literary texts at the junior high school level. The research method used is development research (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects consisted of 60 students divided into experimental and control groups. Data was collected through literary text comprehension tests, interviews, and observations. The research results show that the use of interactive e-books significantly increases students' understanding of literary texts. The experimental group experienced an increase in understanding of 23%, while the control group only increased by 8%. Data analysis also revealed that students were more motivated and active in reading and understanding literary texts when using interactive media. These results are in line with the Cognitive Theory of Multimedia Learning (CTML) theory which states that the combination of visual and text elements can increase students' cognitive engagement. The implication of this research is the importance of developing technology-based learning media to increase the effectiveness of literature learning. Further research can be carried out to develop interactive e-books with more complex features to expand the scope of learning.